EFFECT OF OPERATING PARAMETERS OF HYDRAULIC FRACTURING ON FRACTURE GEOMETRY AND FLUID EFFICIENCY IN OLIGOCENE, OFFSHORE VIETNAM - Nguyen, Truong Huu (Vietnam Journal of Marine Science and Technology, 2016)
In the past decades, a large amount of oil production in the Cuu Long basin was mainly exploited from the basement reservoir, oil production from the Miocene sandstone reservoir and a small amount of oil production from the Oligocene sandstone reservoir. Many discovery wells and production wells in lower Tra Tan and Tra Cu of Oligocene sandstone had high potential for oil and gas production and reserve where the average reservoir porosity was in range of 10% to 18%, and reservoir permeability was in range of 0.1 md to 5 md. Due to high reservoir heterogeneity, complication and complexity of the geology, high closure pressure was up to 7,700 psi. The problem in the Oligocene reservoir is very low fracture conductivity due to low conductivities among the fractures of the reservoirs. The big challenges deal with this problem of hydraulic fracturing stimulation to improve oil and gas production that is required of the study. In this article, the authors have presented the effects of operating parameters as injection time, injection rate, and leak-off coefficient of hydraulic fracturing based on the 2D PKN-C fracture geometry account for leak-off coefficient, spurt loss in terms of power law parameters on the fracture geometry. By the use of design of experiments (DOE) and application of response surface methodology in the constraint of operating hydraulic fracturing parameter of the field experience, the effects plots are evaluated. In the recent years, from the successful application of the hydraulic fracturing stimulation for well completion in the Oligocene reservoir, this technology is often used to stimulate reservoir.